Partisipasi Pedagang dalam Pengelolaan Sampah di Pasar Pinaesaan Kecamatan Tompasobaru (Participation of Traders in Waste Management at Pinaesaan Market Tompasobaru SubDistrict) - Marselino Jeheskiel Lila; Nordy F. L. Waney; Gene H. M. Kapantow (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to determine the level of participation of traders in waste management at Pinaesaan Market, Tompasobaru District. This research was conducted for 3 months starting from February to May 2021. A total of 42 traders were selected as respondents with a simple sampling method (Simple Random Sampling). The data in this study are primary data and secondary data. Primary data was obtained through interviews with traders at Pinaesaan Market, Tompasobaru sub-district using a list of questions that had been prepared in advance. Secondary data was obtained from the Head of Pinaesaan Market, Tompasobaru District. Data analysis was carried out descriptively and presented in the form of a frequency distribution table. The research results showed that in general the level of participation of traders at Pinaesaan Market, Tompasobaru District in waste management was classified in the "Medium Participation" category with a total score of 770 from the highest possible score of 1260. Of the 10 participation indicators studied, there are 2 indicators that fall into the level category. participation is high, 4 indicators of participation rate are low, and the other 4 indicators are in the medium category. Therefore it is necessary to make efforts to increase the awareness of traders to participate more. This effort can be done persuasively and/or repressively. Persuasively, namely by increasing the awareness of traders through increasing socialization about the importance of managing waste together and repressively, by giving strict sanctions to traders who do not comply.